1989
DOI: 10.1007/bf01091937
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and digestibility changes in sprouted barley and canola seeds

Abstract: Barley and canola seeds were sprouted over a 5 day period, in laboratory conditions under room temperature (22 degrees C) and room lighting. Following initial hydration, seeds were kept moist by wetting the germination trays at 9 a.m., 1 p.m. and 6 p.m. daily. A parallel germination experiment using 200 g quantities of seeds in petri dishes was conducted. Starting from the second day of germination, and every day, dishes of germinating seeds were removed, oven-dried, weighed and milled for proximate and chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 13 publications
10
51
1
1
Order By: Relevance
“…Changes in fi ber content may attribute to the fact that part of the seed fi ber may be solubilized enzymatically during seed germination (El Maki et al, 1999). These results are in agreement with Chung et al (1989) who found that the fi bre content increased from 3.75% in unsprouted barley seed to 6% in 5-day sprouts. The carbohydrate content decreased from 48.70% in raw samples to 46.27, 44.56, 43.33 and 41.69 in seeds sprouted for 3, 4, 5 and 6 days, respectively.…”
Section: Resultssupporting
confidence: 88%
“…Changes in fi ber content may attribute to the fact that part of the seed fi ber may be solubilized enzymatically during seed germination (El Maki et al, 1999). These results are in agreement with Chung et al (1989) who found that the fi bre content increased from 3.75% in unsprouted barley seed to 6% in 5-day sprouts. The carbohydrate content decreased from 48.70% in raw samples to 46.27, 44.56, 43.33 and 41.69 in seeds sprouted for 3, 4, 5 and 6 days, respectively.…”
Section: Resultssupporting
confidence: 88%
“…In order to maximize the content of phytosterols, squalene and tocopherols in plant foods, it is important to consider factors such as processing conditions, cultivar, growing season and planting location [25,[38][39][40][41][42][43]. In addition, enhanced contents of these bioactive components may be achieved through crop engineering [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…Increases in the content of polyunsaturated fatty acids in wheat and of dietary fiber in wheat and mung beans were noted. Similarly, Chung, Nwokolo, and Sim (1998) reported that in barley (but not in canola), sprouting was associated with significant increases in crude fiber. Badshah et al (1991) noted significant losses in lipid content during canola sprouting.…”
Section: Article In Pressmentioning
confidence: 94%